The Resilience of MSME Actors Fostered by Rumah BUMN in Malang City: A Social Welfare Perspective - Indira Sukma Wardhani (GoAcademica Research & Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) represent a strategic sector that contributes significantly to economic growth, employment generation, and the improvement of social welfare. However, technological advancements, market transformations, and economic uncertainty require MSME actors to possess the capacity to survive and adapt to various challenges. This capacity is referred to as resilience. This study aims to describe the level of resilience among MSME actors fostered by Rumah BUMN Malang City from the perspectives of personal, social, and business characteristics within the framework of social welfare. The study employed a descriptive quantitative approach involving 400 MSME actors assisted by Rumah BUMN Malang City as respondents. Data were collected through questionnaires and analyzed using descriptive statistics, including frequencies, percentages, and mean values. The findings reveal that the majority of respondents demonstrated a high level of resilience (67.8%). Based on the dimensions of resilience, the resistance aspect recorded the highest mean score (M = 3.797), followed by adaptation (M = 3.770) and recovery (M = 3.725). These findings indicate that MSME actors possess strong capabilities in maintaining business continuity, adapting to changes, and recovering business conditions when facing obstacles. From a social welfare perspective, high resilience reflects the ability of MSME actors to sustain their social and economic functioning through the utilization of individual, family, and social environmental resources. The Rumah BUMN program plays a significant role in strengthening adaptive capacity through training, mentoring, and business network development.